Aflatoxin M1 in fresh milk collected from local markets of Karachi, Pakistan. Issue 3 (3rd July 2018) - Asghar, Muhammad Asif; Ahmed, Aftab; Asghar, Muhammad Arif
ABSTRACT: During 2016–2017, 156 samples of fresh milk samples were collected from local markets of Karachi, Pakistan and analysed for aflatoxin M1 (AFM1 ) contamination using ELISA technique. AFM1 was detected in 143 (91.7%) samples, ranged from 20 to 3090 ng L −1 with a mean level of 346.2 ng L −1 . In 125 (80.1%) samples, the AFM1 contamination was greater than the maximum limit (ML = 50 ng L −1 ) set by EU. However, in 51 (32.7%) samples, the AFM1 level was higher than the ML of 500 ng L −1 as assigned by the USA. Statistical analysis showed that the AFM1 level in milk samples from summer was significantly ( p  < 0.05) higher than that obtained in winter. It was concluded that the AFM1 levels in the tested samples appear to be a serious public health problem. Therefore, immediate measures should be taken and re-evaluation done for the procedures for farming, transportation, refrigeration, and storage for the control of AFM1 level in milk samples.